2006
DOI: 10.1534/genetics.106.056721
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Identities of the Caenorhabditis elegans Intraflagellar Transport Genes dyf-6, daf-10 and osm-1

Abstract: The Caenorhabditis elegans genes dyf-6, daf-10, and osm-1 are among the set of genes that affect chemotaxis and the ability of certain sensory neurons to take up fluorescent dyes from the environment. Some genes in this category are known to be required for intraflagellar transport (IFT), which is the bidirectional movement of raft-like particles along the axonemes of cilia and flagella. The cloning of dyf-6, daf-10, and osm-1 are described here. The daf-10 and osm-1 gene products resemble each other and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 36 publications
(59 reference statements)
4
59
0
Order By: Relevance
“…In contrast, daf-19 mutants (we tested m86, rh1024, and sa232) move only for a short time and then start feeding locally ( Figure 4D; data not shown). A similar behavior is observed in many (Bell et al, 2006; Figure 4C; data not shown). To test the functions of the different DAF-19 isoforms in the dwelling/roaming behavior, we generated isoform-specific rescue constructs ( Figure 4I).…”
Section: Dwelling/roaming Behavior Depends On Multiple Daf-19 Isoformssupporting
confidence: 87%
“…In contrast, daf-19 mutants (we tested m86, rh1024, and sa232) move only for a short time and then start feeding locally ( Figure 4D; data not shown). A similar behavior is observed in many (Bell et al, 2006; Figure 4C; data not shown). To test the functions of the different DAF-19 isoforms in the dwelling/roaming behavior, we generated isoform-specific rescue constructs ( Figure 4I).…”
Section: Dwelling/roaming Behavior Depends On Multiple Daf-19 Isoformssupporting
confidence: 87%
“…While transgenic animals grown at 20°failed to take up DiI, dye filling was observed exclusively in the two sra-6-expressing neurons 8 hr after heat shock (Figure 3), suggesting that hsf-1 and che-2 indeed function cell autonomously. A similar conclusion was reached for the cilia gene dyf-6 (Bell et al 2006). In both osm-6 and sra-6 transgenic lines, rescue was very efficient, reaching nearly 90% in some lines (Table 1).…”
supporting
confidence: 74%
“…Here, we used a model organism, C. elegans. In C. elegans, 60 of the 302 neurons of the hermaphrodite are ciliated sensory neurons, and several works have demonstrated that the mutants of IFT-related genes show defects in sensory functions (Cole et al 1998;Signor et al 1999;Qin et al 2001;Haycraft et al 2003;Schafer et al 2003;Blacque et al 2004;Scholey et al 2004;Snow et al 2004;Ou et al 2005;Bell et al 2006;Evans et al 2006). In the present work, we identified nematode IFT-81 and IFT-74, whose C. reinhardtii orthologues were recently shown to form core complex in subcomplex B (Lucker et al 2005), and attempted to elucidate their physiological roles in C. elegans.…”
Section: Introductionmentioning
confidence: 81%